ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN PROVINSI JAWA TIMUR : PENDEKATAN ERROR CORRECTION MODEL - Sinta Zahrotussolichah; Yustirania Septiani (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to analyze the factors that influence poverty in East Java Province. This data analysis utilizes the ECM (Error Correction Model) method to see the effect of long-term and short-term prospects with the Eviews 10 application. This observation uses secondary data in the form of time series data published by BPS in 2000 – 2021. The results reveal that the education level variable has an influence positive and significant for poverty both in the long-term and short-term prospects, the open unemployment rate variable has a positive and significant effect on poverty in the long and short term, and the minimum wage variable has a negative and significant effect on the long-term prospects on the other hand in the long-term prospects short has no significant effect on poverty.